Factors Associated With Continuous Low-Dose Heparin Infusion for Central Venous Catheter Patency in Critically Ill Children Worldwide. Issue 8 (August 2016) - Onyeama, Sara-Jane N.; Hanson, Sheila J.; Dasgupta, Mahua; Hoffmann, Raymond G.; Faustino, Edward Vincent S.
Abstract : Objectives: To identify patient, hospital, and central venous catheter factors that may influence the use of low-dose heparin infusion for central venous catheter patency in critically ill children. Design: Secondary analysis of an international multicenter observational study. Setting: Fifty-nine PICUs over four study dates in 2012, involving seven countries. Patients: Children less than 18 years old with a central venous catheter who were admitted to a participating unit and enrolled in the completed Prophylaxis against Thrombosis Practice study were included. All overflow patients were excluded. Interventions: None. Measurements and Main Results: Of the 2, 484 patients in the Prophylaxis against Thrombosis Practice study, 1, 312 patients had a central venous catheter. Five hundred seven of those patients used low-dose heparin infusion. The frequency of low-dose heparin infusion was compared across various patient, hospital, and central venous catheter factors using chi-square, Mann-Whitney U, and Fisher exact tests. In the multivariate analysis, age was not a significant factor for low-dose heparin infusion use. Patients with pulmonary hypertension had decreased low-dose heparin infusion use, whereas those with active surgical or trauma diagnoses had increased low-dose heparin infusion use. All centrally inserted central venous catheters were more likely to use low-dose heparin infusion when compared with peripherally inserted central venous catheters. The Asia-Pacific region showed increased low-dose heparin infusion use, along with community hospitals and smaller ICUs (< 10 beds). Conclusions: Patient, central venous catheter, and hospital factors are associated with the use of low-dose heparin infusion in critically ill children. Further study is needed to evaluate the efficacy and persistence of low-dose heparin infusion use.